Exploratory Considerations in Chemistry Education-Didactic Modelling for Complexity in Students' Discussions - Dudas, C.; Rundgren, C. J.; Lundegård, I.
Research has shown the importance of dealing with real-life issues and of enabling student encounters with complexity in chemistry education in order to increase student participation. Therefore, this study aims to analyse how complexity evolves in students' discussions and how this complexity relates to aspects of tentativeness in chemistry. In the study, we analyse how a previously developed didactic model can be refined from the students' considerations evolving from the present context. The study was conducted as an in situ study in one upper-secondary school. Students' discussions were recorded on video. The recordings were transcribed and analysed using deliberative educational questions. Two different kinds of considerations emerged in the students' discussions: factual and exploratory considerations. While factual considerations are an important element of chemistry education, students also need to encounter exploratory considerations. The study proposes a didactic model useful for teachers in didactic analysis and design of activities aiming to support students to unfold complexity through exploratory considerations. One implication is to base activities on real-life issues in order to invite the unpredictability needed for experiencing complexity and the exploratory nature of chemistry. These issues enable students to experience aspects of tentativeness in chemistry and thereby increase their understanding of NOS and chemistry as a knowledge building practice. Furthermore, this might also increase student participation in chemistry education.
Keywords: CHEMISTRY EDUCATION; UPPER-SECONDARY EDUCATION; DIDACTIC MODELLING; COMPLEXITY; SCIENTIFIC LITERACY